Implicações do odor na percepção e escolha de parceiro - Moura, Tomaszewski Hipolito de (2007)
Why are we attracted to some people but not to other ones? How is this attraction established? Which signs are characteristic of a good partner? These and many other questions concerning how mate attraction and mate selection work out among humans have been intriguing behavioral scientists. It is well-known that beauty indicates something about a potential mate s health. The odor may indicate a similar assessment, if we can assess how pheromones are integrated into human sexual behavior. However, what is the relation between age preference and body scent evaluation? In order to investigate this question, this study´s objective was identifying evidences which show that olfactory cues might reveal the potential mate s age and that it coincides with the ideal mate s profile. To produce the stimuli, men and women had to wear cotton t-shirts for three nights in order to have their body odor impregnated. After that, opposite-sex individuals evaluated the intensity and attractivity of these odor impregnated tshirts according to two Likert scales (4 points scale for intensity; 7 points scale for attractivity). We found differences between men and women on body scent perception, that indicates a better scent discrimination for women when it concerns the perception of potential mate s age. Another finding was the negative correlation between intensity and attractiveness perception for both sexes. We also verified that mate selection strategies are plural, more than one tactic simultaneously fitting in the same strategy, but all of them are related to differential investment of each sex on their own reproductive success